Adaptive-gain fast super-twisting sliding mode fault tolerant control for a reusable launch vehicle in reentry phase. (November 2017) - Zhang, Yao; Tang, Shengjing; Guo, Jie
Abstract: In this paper, a novel adaptive-gain fast super-twisting (AGFST) sliding mode attitude control synthesis is carried out for a reusable launch vehicle subject to actuator faults and unknown disturbances. According to the fast nonsingular terminal sliding mode surface (FNTSMS) and adaptive-gain fast super-twisting algorithm, an adaptive fault tolerant control law for the attitude stabilization is derived to protect against the actuator faults and unknown uncertainties. Firstly, a second-order nonlinear control-oriented model for the RLV is established by feedback linearization method. And on the basis a fast nonsingular terminal sliding mode (FNTSM) manifold is designed, which provides fast finite-time global convergence and avoids singularity problem as well as chattering phenomenon. Based on the merits of the standard super-twisting (ST) algorithm and fast reaching law with adaption, a novel adaptive-gain fast super-twisting (AGFST) algorithm is proposed for the finite-time fault tolerant attitude control problem of the RLV without any knowledge of the bounds of uncertainties and actuator faults. The important feature of the AGFST algorithm includes non-overestimating the values of the control gains and faster convergence speed than the standard ST algorithm. A formal proof of the finite-time stability of the closed-loop system is derived using the Lyapunov function technique. An estimation of the convergence time and accurate expression of convergence region are also provided. Finally, simulations are presented to illustrate the effectiveness and superiority of the proposed control scheme. Highlights: Based on the fast nonsingular terminal sliding mode surface and adaptive-gain fast super-twisting algorithm, a novel integrated finite time sliding mode control law for the attitude stabilization is derived for a reusable launch vehicle subject to actuator faults and unknown disturbances. The proposed method provides rapidly finite time global convergence, avoids singularity problem successfully and non-overestimates the values of the control gains without any knowledge of the faults and disturbances. Simulations results are presented to illustrate the effectiveness and superiority of the proposed control scheme.